Comparative analysis of bio-binder properties derived from different sources. Issue Volume 20:Issued 7(2019) (3rd July 2019) - He, Min; Tu, Cheng; Cao, Dong Wei; Chen, Yan Ju
ABSTRACT: Chemical composition of bio-binders derived from three different representative biomass sources has been characterised and compared by elemental analysis, Fourier Transform Infrared, 1 H NMR and Vapor pressure osmometry. Three bio-binders were then added into matrix asphalt to produce different blended asphalt. Physical properties, thermal storage stability and rheological properties of blended asphalt have been tested and comparatively analysed. Chemical characterisation results show that three bio-binders are all carbon-rich hybrids containing large amounts of oxygen-containing compounds. Among the three bio-binders, PB has the highest content of aromatic rings and phenol hydroxyls but the lowest aliphatic content while OB the highest aliphatic content but the lowest aromatic ring and phenol hydroxyl content. Besides, the average molecular weight of PB is the largest whereas OB has the smallest average molecular weight. Physical property, thermal storage stability and rheological property evaluation show all blended asphalt have fairly good thermal storage stability. The addition of each bio-binder can improve high-temperature performance of matrix asphalt whereas the low-temperature performance of matrix asphalt will be slightly harmed. PB has the strongest effects on improving the high-temperature performance of matrix asphalt and worsening the low-temperature performance of matrix asphalt while OB is on the contrary.